GAMBARAN INDEKS KEBERSIHAN GIGI DAN MULUT PADA ANAK PENDERITA DOWN SYNDROME DISALAH SATU SLB DI KOTA BANDUNG (Jurnal Kesehatan Siliwangi, 2020)
Children with special needs are children who have intellectual, mental and / or sensory limitations. One of them is a child who has mental limitations, Down syndrome. The purpose of this study was to analyze the index of dental and oral hygiene in children with Down Syndrome in one SLB in the city of Bandung. This type of research is descriptive. The sample in this study was taken by accidental sampling, the number of samples of 6 people. The data generated is processed and presented in the form of a frequency distribution table. The results showed that the index of dental and oral hygiene in children with Down syndrome in one SLB in the city of Bandung was 33% good, and 67% were moderate. Keywords: index of dental and oral hygiene, and down syndrome